2009
DOI: 10.1038/jhg.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel L2HGDH gene mutations and update of the pathological spectrum

Abstract: L-2-hydroxyglutaric aciduria (L-2-HGA, MIM 236792) is a neurometabolic disorder caused by the toxic accumulation of high concentration of L-2-hydroxyglutaric acid in plasma and cerebrospinal fluid. Distinct mutations on the L2HGDH gene have been associated with the clinical and biochemical phenotype. Here we present three novel mutations (Gln197X, Gly211Val and c.540+1 G4A), which increase the present deleterious collection of L2HGDH gene up to 35 mutations that we have compiled in this study. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The diagnosis of L2HGA comprises of biochemical, radiological and genetic testing. The MRI abnormalities seen in the subcortical cerebral white matter, putamen, caudate nucleus, globus pallidus, and dentate nucleus are unique to L2HGA, and are used as baseline investigation [ 6 , 10 16 ]. The disease-causing gene is L-2-hydroxyglutarate dehydrogenase ( L2HGDH -NM_024884.2) which is located on chromosome 14q22.1 [MIM 609584] and comprises of 10 coding exons spanning 75 kb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of L2HGA comprises of biochemical, radiological and genetic testing. The MRI abnormalities seen in the subcortical cerebral white matter, putamen, caudate nucleus, globus pallidus, and dentate nucleus are unique to L2HGA, and are used as baseline investigation [ 6 , 10 16 ]. The disease-causing gene is L-2-hydroxyglutarate dehydrogenase ( L2HGDH -NM_024884.2) which is located on chromosome 14q22.1 [MIM 609584] and comprises of 10 coding exons spanning 75 kb.…”
Section: Introductionmentioning
confidence: 99%
“…L2HGDH is a mitochondrial enzyme which catalyses oxidation of L-2-hydroxyglutarate (L2HG) to α2-ketoglutarate (α2KG); a metabolic product bound to mitochondrial membrane [ 15 , 17 ]. Several mutations L2HGDH have been reported worldwide in affected individuals belonging to various ethnic groups [ 6 , 8 , 13 16 , 18 , 19 ] ( http://grenada.lumc.nl/LOVD2/vumc/status.php ) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 10 Haplotyping showed that the Portuguese and Italian patients shared the mutation-carrying chromosome with identical SNP haplotypes, thus pointing to a common origin of the mutation in these 2 populations. 10 The Italian and Portuguese patients carried the c.159C allele (c.159T/C SNP, which is located 10 nucleotide upstream of the pathogenic c.169G>A mutation. 9 The finding of the homozygous c.159T allele associated with the c.169G>A mutation in Arab patients points to an independent origin of the c.169G>A mutation in Arab population.…”
Section: Discussionmentioning
confidence: 93%
“… 6 8 , 10 In a recent study, the c.169G>A mutation (p.Gly57Arg) that was originally found in a compound heterozygous state in a Portuguese female was discovered in a homozygous state in an Italian male patient. 7 , 10 Haplotyping showed that the Portuguese and Italian patients shared the mutation-carrying chromosome with identical SNP haplotypes, thus pointing to a common origin of the mutation in these 2 populations. 10 The Italian and Portuguese patients carried the c.159C allele (c.159T/C SNP, which is located 10 nucleotide upstream of the pathogenic c.169G>A mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation